Pembiasaan sikap bersalaman pada anak di PAUD Dharmawanita Kabupaten Lebong - Yuliana Prakasa (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this research is to describe the shaking hands habitual on children at PAUD dharma wanita in Lebong regency. This research is a descriptive research and uses qualitative approach. Data are words, pictures, not numbers. The subject of this research is 15 children. The method which used is introduction of greeting behavior which conducted every day.The result of this research is the handshakes behavior is implemented since the school was built. It can be seen that children mostly use right hand to hand shake, followed by greeting and polite act. They mostly do this before entering the class, apologizing to friend. Children also taught to hand shake the older by shaking their hands, hold their hands with two hands, being polite as mentioned in AL-Quran. It is good to have smiling face while handshaking and not to pull out the hands before the he/she pull out his/her hands.